THE INFLUENCE OF JIGSAW TECHNIQUE ON IMPROVING READING COMPREHENSION FOR STUDENTS OF NON-ENGLISH DEPARTMENTS STKIP AL MAKSUM - Donny Adiatmana Ginting; Elissa Haddina; Khairunnisa Br. Malau (The Seall Journal, 2022)
The main problem of students in non-English departments is that they hardly find the theme, main idea and are bored in reading activity. The aim is to find the influence of the jigsaw technique on improving student’s reading comprehension in non-English departments. The research method is pre-experimental research with one group design pretest and posttest. The sample is 45 students in an elementary education study program. The instrument is multiple choice with ten questions. The data analysis shows the questions are valid and reliable. The mean score of the pretest and posttest shows significant differences. Based on paired dependent t-test, the value is 0.000 lower than 0.05 as the level of significance and therefore, there is the influence of the jigsaw technique on Improving Reading Comprehension for Students' of Non-English Departments. Based on findings, the jigsaw technique is suggested to be used in teaching reading for non-English departments. Keywords: jigsaw, reading comprehension, non-English department